2022
DOI: 10.4103/ijcm.ijcm_1275_21
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Epidemiology of Unintentional Childhood Injury at One of the Districts of Gujarat State

Abstract: Context: Childhood injuries are a less explored area of public health. In the presence of public health problems such as communicable and noncommunicable diseases, childhood injury has gained less attention from the health system. Aims: The aim of the study was to assess the prevalence of various types of unintentional injuries (UI) amongst children and to assess the factors associated with same. Settings and Design: The study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The vast majority of children had one fracture, but some children had more than one. Similar findings were reported by Dave et al [21], as fall-related injuries had the highest prevalence (3.38%), followed by road traffic injuries (RTI) (1.62%). In Saudi Arabia, Albedewi et al [22] reported that falls represented 31.9% of childhood injuries, while 25.1% were due to motor vehicle collisions (MVC).…”
Section: Discussionsupporting
confidence: 89%
“…The vast majority of children had one fracture, but some children had more than one. Similar findings were reported by Dave et al [21], as fall-related injuries had the highest prevalence (3.38%), followed by road traffic injuries (RTI) (1.62%). In Saudi Arabia, Albedewi et al [22] reported that falls represented 31.9% of childhood injuries, while 25.1% were due to motor vehicle collisions (MVC).…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis of the timing of injuries found that 423 cases (44.5%) occurred between 12 PM and 6 PM, and Saturdays (96 cases, 20.6%) and Sundays (162 cases, 17.0%) showed signi cantly higher incidences than weekdays, indicating a heightened rate of trauma during non-working days. Furthermore, studies in developing countries have identi ed inadequate supervision, lower safety standards of household items, insu cient public safety warnings, and uneven road surfaces as risk factors for paediatric trauma [31,32]; these issues necessitate a more comprehensive investigation to better understand the myriad causes of child injuries in low-and middle-income nations [33,34]. Seasonally, winter showed a relatively lower trauma incidence, likely due to reduced outdoor activities because of colder weather.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentric national level study on epidemiology of unintentional childhood injury in India indicated that fall-related injuries had the highest prevalence (22). Fall injuries are one of the common diseases in the pediatric emergency department, and the main cause of long-term disability in children (23).…”
Section: Discussionmentioning
confidence: 99%